2017
DOI: 10.1021/acs.est.7b03113
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Passive Sampling of POP in Lipid-Rich and Lean Fish Tissue: Quality Control Using Performance Reference Compounds

Abstract: Passive sampling is widely used to measure levels of contaminants in various environmental matrices, including fish tissue. Equilibrium passive sampling (EPS) of persistent organic pollutants (POP) in fish tissue has been hitherto limited to application in lipid-rich tissue. We tested several exposure methods to extend EPS applicability to lean tissue. Thin-film polydimethylsiloxane (PDMS) passive samplers were exposed statically to intact fillet and fish homogenate and dynamically by rolling with cut fillet c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…EPS was applied by equilibrating >1 kg of fillet cubes or >0.2 kg liver tissue pieces and SSP passive samplers (S7-1), as described in S8-3. 17 After the extraction of SSP (S8-4), cleanup (S8-5), and instrumental analysis (S8-6), the equilibrium HOC concentrations in SSP were converted to lipid basis (C L⇌tissue ) by multiplying with the lipid (triolein/fish oil)−polymer partition coefficient (K LP ) for SSP. For neutral lipids, these K LP values are not lipid-specific and are available for PCB, PeCB, HCB, and DDx.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPS was applied by equilibrating >1 kg of fillet cubes or >0.2 kg liver tissue pieces and SSP passive samplers (S7-1), as described in S8-3. 17 After the extraction of SSP (S8-4), cleanup (S8-5), and instrumental analysis (S8-6), the equilibrium HOC concentrations in SSP were converted to lipid basis (C L⇌tissue ) by multiplying with the lipid (triolein/fish oil)−polymer partition coefficient (K LP ) for SSP. For neutral lipids, these K LP values are not lipid-specific and are available for PCB, PeCB, HCB, and DDx.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…EPS provides data equivalent to C L in fish fillet measured after classical solvent extraction. 16,17 Note that C L⇌water or C L⇌sediment should not be understood as a direct prediction of internal HOC concentration in aquatic organisms but rather as the thermodynamic HOC level in the monitored habitat the fish is exposed to. The thermodynamic level of persistent HOCs, expressed as C L , is often observed to increase from primary producers, through primary consumers, toward predators, and a log-linear relationship with the TL can be fit to these observations 5…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a consequence, equilibrium is not attained within a week . This issue can be overcome by multiple manual relocations of the silicone to assure that a fresh tissue is constantly in contact with the sampler. , However, this bears the risk of sample contamination and involves time-intensive laboratory logistics. Rolling thin PDMS sheets in jars together with tissue cubes or homogenates is an alternative sampling method for lean fish tissues. , …”
Section: Introductionmentioning
confidence: 99%
“…Rolling thin PDMS sheets in jars together with tissue cubes or homogenates is an alternative sampling method for lean fish tissues. 27,29 PDMS extracts can be subjected without extensive cleanup to instrumental analysis 30 and bioanalytical screening 21,23,26 because only small amounts of unwanted matrices are coextracted. Especially in toxicological screening studies using cell-based in vitro bioassays, conserving the original mixture composition is important because the losses of analytes during cleanup stages cannot be corrected with recovery standards and extensive extraction and cleanup procedures might cause contamination and blank effects.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The performance of passive samplers to predict concentrations of persistent contaminants in organisms other than bivalves was considered for some time as unclear (USEPA, 2012a;ICES, 2013). However, more recent studies have found good agreement between concentrations in passive equilibrium samplers (PES) and those in fish (Cerveny et al, 2016;Rusina et al, 2017). This opens the possibility of finding similar results for other organisms, allowing biota monitoring to be supplemented by PES and improving contaminant modelling and risk assessment at the higher trophic levels.…”
Section: Introductionmentioning
confidence: 90%